Epidemiological profile of candidiasis in HIV/AIDS patients in a tertiary care hospital - Dhakad, Megh S.; Kaur, Ravinder; Goyal, Ritu; Bhalla, Preena; Dewan, Richa (International Journal Of Community Medicine And Public Health, 2020)
Background: Clinical research in fungal infections is largely a neglected area in health care settings in India. Candida species cause diseases ranging from mucosal infections to systemic mycoses depending on host’s immune status. Aim of this study was to evaluate the clinico-epidemiological profile of candidiasis, and their correlation with an immunological profile in HIV/AIDS patients. Methods: Clinical details and investigations of 200 symptomatic, confirmed HIV-positive patients, suspected of having candidiasis were recorded and analyzed. Relevant clinical samples depending on the organ system involved were collected and subjected to direct microscopy, culture isolation and serology. Identification and speciation of the isolates was done by biochemical methods as per standard recommended procedures. CD4-count was determined by flow cytometry using Fluorescent Activated Cell Sorter Count system. Results: Patients ranged from 17-65 years with a mean age of 33.83±9.07 years. Most common clinical presentations were seen to be white oral patches (82%), weight loss (79%), fever (67%), loss of appetite (53%), headache (51.5%), cough (38.5%) and diarrhea (30%). Gastrointestinal system (35%) was the most commonly involved system. The CD4-counts ranged from 16-1033 cells/μl. 93 (46.5%) patients had CD4-counts <200 cells/μl, while CD4-count <100 cells/μl was seen in 40 (20%) and CD4-count <50 cells/μl in 20 (10%). Candidiasis was detected in 60% of the patients. Yeasts isolated were C. albicans (82.51%), C. tropicalis (6.29%), C. krusei (4.89%), C. parapsilosis (3.49%), and C. glabrata (2.79%). Conclusions: C. albicans was predominant species and presence of oral candidiasis is a matter of concern. Early and accurate diagnosis of candidiasis is one of the keys helps for the success of effective HIV/AIDS disease management.